GAMBARAN PASIEN HIRSCHSPRUNG DI RSUP PROF. DR. R. D. KANDOU MANADO PERIODE JANUARI 2010 – SEPTEMBER 2014 - Corputty, Elfianto D.; Lampus, Harsali F.; Monoarfa, Alwin (e-CliniC, 2015)
Abstract: Hirschsprung disease is a developmental disorder of the intrinsic component of the enteric nervous system that is characterized by the absence of ganglion cells in the myenteric and submucosal plexuses of the distal intestine. Because these cells are responsible for normal peristalsis, patients with Hirschsprung disease present with functional intestinal obstruction at the level of aganglionosis. This researched purpose to know the description of Hirschsprung ddisease patient in RSUP Prof. Dr. R. D. Kandou Manado for period January 2010 to September 2014. The research method used was a descriptive retrospective. This study found 45 cases of Hirschsprung Disease. Males are more than females with ratio 1,3:1 with the age group are from 2 day to 45 years old. Most Hirscshprung disease patients came with the main complaints: abdominal distension, difficult to defecate and not defecation from birth, with the concomitant complaints, that is vomiting and abdominal pain. The most supporting examination of Hirscshprung disease is radiologic evaluation, that is plain abdominal x-ray and barium enema, and patologi anatomi evaluation, that is mucosal biopsy and suction biopsy. The most used surgery technique of Hirscsprung disease patients is colostomy and duhamel procedure. The most frequent complication of Hirschsprung disease is sepsis. The most outcome is improved clinical condition.Keywords: Hirschsprung disease, description of patientAbstrak: Penyakit Hirschsprung merupakan kelainan perkembangan komponen intrinsik pada sistem saraf enterik yang ditandai oleh absennya sel-sel ganglion pada pleksus myenterik dan submukosa di intestinal distal. Karena sel-sel ini bertanggung jawab untuk peristaltik normal, pasien-pasien penyakit Hirschprung akan mengalami obstruksi intestinal fungsional pada level aganglion. Tujuan Penelitian ini untuk mengetahui gambaran pasien Hirschsprung di RSUP Prof. Dr. R. D. Kandou Manado periode Januari 2010 sampai September 2014. Metode penelitian ini bersifat deskriptif retrospektif. Pada penelitian ini ditemukan 45 kasus penyakit Hirschsprung. Laki-laki lebih banyak dari perempuan dengan rasio 1,3:1 dengan umur mulai dari 2 hari sampai 45 tahun. Secara umum, pasien Hirschsprung datang dengan keluhan utama yaitu perut kembung, tidak BAB sejak lahir dan sulit BAB, disertai keluhan penyerta yaitu muntah atau nyeri perut. Secara umum pemeriksaan penunjang yang digunakan adalah pemeriksaan radiologi yaitu foto polos abdomen dan barium enema, dan pemeriksaan patologi anatomi yaitu biopsi eksisi dan biopsi hisap. Sebagian besar pasien Hirschsprung dilakukan tindakan bedah kolostomi dan duhamel. Komplikasi pada umumnya adalah sepsis. Hasil akhir penatalaksanaan pada umumnya cukup baikKata kunci: penyakit hirschsprung, gambaran pasien